Impulsivity mediates the relationship between childhood maltreatment and quality of life: Does social support make it different?. (January 2022) - Gao, Tingting; Mei, Songli; Li, Muzi; O'Donnell, Kieran; Caron, Jean; Meng, Xiangfei
Abstract: This cross-sectional study aimed to investigate the mediating effect of impulsivity as well as the moderating effect of social support in the association between childhood maltreatment and quality of life (QoL). Data analyzed were from a large community-based cohort. The study sample included 1402 participants with 512 males and 890 females aged from 17 to 79 years ( M  = 50.61, SD  = 13.77). All participants in the cohort provided informed consent and the study received ethical approval prior to the data collection. The core studied variables were childhood maltreatment, impulsivity, social support, and QoL. Moderated mediation analysis was used to examine the relationships among the studied variables. The study found that impulsivity partially mediated the association between childhood maltreatment and QoL. The mediation effect accounted for 21.56% of the total effect of the association between childhood maltreatment and QoL. Social support only moderated the direct path of childhood maltreatment and QoL. Prevention and intervention efforts should promote a warm social environment to improve the level of social support and provide adaptive coping strategies among individuals with high impulsivity or with a history of maltreatment. Highlights: Impulsivity mediated the association between maltreatment and quality of life. Social support only moderated the direct path of child maltreatment and quality of life. Prevention solutions should focus on social support to promote better quality of life. Individuals with high impulsivity with maltreatment history should be prioritized.